Peurs et aspiration à l’émigration à Miami et à Barcelone des Argentins de la classe moyenne (1999-2003) - Cécile Vermot (Les Cahiers ALHIM)
The aim of this article is to analyze the role of fear in the aspirations to the emigration for the “losers” of the “Memem’s party”. To what representations is it related in the narrative of their mobility? What was its role in their aspiration to emigration? Is its expression linked to the migratory act? To migrant status? 52 semi-directive interviews with Argentine migrants who left their country between 1999 and 2003 were conducted in Spanish. 30 interviews were conducted in Miami and 22 interviews in Barcelona. The results show that fear is mobilized in three different ways in the discourse of migrants. It is linked to a feeling of insecurity about delinquency in Argentina, a feeling of vulnerability and powerlessness vis-à-vis economic and political uncertainty, and finally, the risk of migration. Taking account of fear from a sociological point of view contributes to the intelligibility of the migratory process of these middle class Argentines. Indeed, these fears are linked to representations specific to this part of the middle class according to the gender of the individuals and during this socio-historical period.